2020
DOI: 10.1080/08897077.2019.1635964
|View full text |Cite
|
Sign up to set email alerts
|

Opioid, Cocaine, and Amphetamine use Disorders are Associated with Higher30-Day Inpatient Readmission Rates in the United States

Abstract: Background: Patients with substance use disorders (SUDs) are more likely to experience serious health problems, high healthcare utilization, and premature death. However, little is known about the contribution of SUDs to medical 30-day readmission risk. We examined the association between SUDs and 30-day all cause readmission among non-pregnant adult in-patients in the US. Methods: We conducted a retrospective study using 2010–2014 data from the Nationwide Readmissions Database. Our primary focus was on opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Consistent with current literature, demographic characteristics (age, gender, and race) did not predict psychiatric readmission 10 11 As per a nationwide study, stimulant-use disorders increases the odds of 30-day all-cause readmission by 20% 12 . Among substance use disorders (SUDs), we found that stimulant abuse/dependence increase the odds for 90-day and annual psychiatric readmission by two times.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with current literature, demographic characteristics (age, gender, and race) did not predict psychiatric readmission 10 11 As per a nationwide study, stimulant-use disorders increases the odds of 30-day all-cause readmission by 20% 12 . Among substance use disorders (SUDs), we found that stimulant abuse/dependence increase the odds for 90-day and annual psychiatric readmission by two times.…”
Section: Discussionsupporting
confidence: 82%
“…10,11 As per a nationwide study, stimulant-use disorders increases the odds of 30-day all-cause readmission by 20%. 12 Among substance use disorders (SUDs), we found that stimulant abuse/dependence increase the odds for 90-day and annual psychiatric readmission by two times. Also, alcohol and cannabis abuse/dependence increased the readmission rates by two times but was statistically not significant which correlated with current literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-discharge consultation appears to be critical; among patients discharged from residential treatment for substance use, the ones attending their initial outpatient appointment within 7 days of discharge evidenced better long-term outcomes relative to patients who did not, with respect to continuous abstinence [ 6 ]. Building a proper continuity of care would help reduce in-patient readmissions, considering that using substances precisely increases the odds of 30-day all-cause readmission (particularly opioid, cocaine, and amphetamine use) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Research found that up to 33% of patients with SUD return to general hospital for all medical reasons combined within 1 month of discharge. 1,2,7 When examining admission for behavioral health reasons 29% of patients with SUD were found to return to hospital after 90 days with the highest number within the first week after discharge. 8 One Swiss study found that 41% of patients with SUD were readmitted to a specialized addiction unit within the year following discharge.…”
Section: Introductionmentioning
confidence: 99%